A Marketing Strategy Analysis of Marketing Strategies to Increase Competitiveness at Kopili Coffee - Melinda Ariadini (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
Abstract This study aims to analyze the marketing strategies carried out by the Kopili Cafe business actors to increase the competitiveness of Kopili Cafe against other cafes as competitors. The research method used in this research is descriptive method. Methods of data collection in this study using interviews, observation, and documentation. The results of the research on Marketing Strategies to Increase Competitiveness at Kopili Coffee, namely the marketing strategy carried out by Kopili Coffee is quite effective in promoting products and developing quality. Kopili Coffee continues to develop its marketing strategy so that it continues to grow and be able to compete in the midst of many competitors.